Influence of the organizational climate in the burnout syndr0me. Regional Hospital Hermilio Valdizan Medrano Huánuco - Alvarado Ortega, Eudonia I. (2019)
Considering that stress is part of our daily life affecting both health and personal well-being as well as job and collective satisfaction. The present work was carried out considering the problem: How does the organizational climate influence the Burnout syndrome of health personnel working at the Surgical and Central Sterilization Center, Hermilio Valdizan Medrano Huánuco 2015 Regional Hospital? The goal was to establish the influence of the organizational climate on the Burnout syndrome of health personnel working at the Surgical and Central Sterilization Center, Hermilio Valdizan Medrano Huánuco Regional Hospital 2015. It belonged to an observational, cross-sectional, and analytical study, due to bivariate analysis was used. The population was 35 professionals. The instruments used were: data col-lection and questionnaire, validated by an expert judgement of five. At the end of the investigation showed that the organizational climate related to self-realization, labor involvement supervision, communication, working conditions and in general the organizational climate. has significant influence on Burnout syndrome. The difficulty in this work was economic, since it was self-financed in its entirety by the author.